The problem of sentience - Candiotto, Laura (Springer, 2024)
Sentience, as the capacity to feel pleasure and pain, is often understood as a property of an organism, and the main problem is to determine whether an organism possesses this property or not. This is not just an armchair worry. Sentient ethics grounds its normative prescriptions on sentience, so assessing if an organism possesses sentience is crucial for ethical reasoning and behaviour. Assessing if it is the case is far from simple and there is no stable agreement about it. This is the problem of sentience. In this paper, I argue that there is a problem intrinsic to the problem of sentience. I call it the “metaproblem of sentience”. I claim that the assumptions that underlie the concept of sentience are what create the “problem of sentience”. In the first part of the paper, I list and describe these assumptions and show how they create the problem of sentience in sentient ethics. In the second part, I offer enactive and pragmatist tools, namely real doubt (Peirce, In: Kloesel C (ed) Writings of Charles S. Peirce: A Chronological Edition, vol. 3. Bloomington: Indiana University Press, 1986) and loving epistemology (De jaegher, Phenomenol Cogn Sci 20:847–870. https://doi.org/10.1007/s11097-019-09634-5, 2019), for tackling the problem of sentience. I advance a participatory account of sentience and show of relevance of the transcendental argument (Weber and Varela, Phenomenol Cogn Sci, 1:97–125, 2002; Weber, Natur als Bedeutung: Versuch Einer Semiotischen Ästhetik Des Lebendigen. Königshausen & Neumann, 2003; Thompson, Mind in life: Biology, Phenomenology, and the sciences of mind. Harvard University Press, 2007) in ethical discourse. My own contribution is that the transcendental argument should be understood in a relational manner, from the experience of participatory sentience. So it is not just that life can be known only by life. Life can be cared for only by life. So, as in sentient ethics, it is out of my concern for sentient begins that I need to care for them. But, distinct from sentient ethics, may approach to participatory sentience would push to known sentience from how I care for sentient begins, from how I engage with them, from how I take part in their life. I conclude by stressing the significance of a participatory ethics of sentience.
Keywords: sentience; loving epistemology; participatory sense-making; participatory ethics; pragmatism; enactivism